Surgical Navigation Improves the Precision and Accuracy of Tibial Component Alignment in Canine Total Knee Replacement. Issue 1 (January 2016) - Peters, Kaleigh M.; Hutter, Erin; Siston, Robert A.; Bertran, Judith; Allen, Matthew J.
Abstract : Objective: The goal of this study was to determine whether computer‐assisted surgical navigation improves the accuracy of tibial component alignment in canine total knee replacement (TKR). Study Design: Retrospective radiographic review and prospective ex vivo study. Sample Population: Canine TKR radiographs (n = 17 sets) and canine cadaveric stifles (n = 12). Methods: Radiographs from TKR surgical workshops were reviewed to determine the incidence and magnitude of tibial component malalignment. Tibial component alignment was compared after either standard ("surgeon‐guided") component placement or computer‐assisted ("navigation‐guided") placement. Results were compared against the current recommendations of a neutral (0° varus–valgus) ostectomy in the frontal plane and 6° of caudal slope in the sagittal plane. A prospective cadaveric study was then undertaken by performing TKR in 12 canine stifle joints. Results: Malalignment of >3° in the frontal and sagittal planes was identified in 12% and 24% of the radiographs from the retrospective review, respectively. Surgical navigation reduced both the mean error ( P = .007) and the variability in frontal plane alignment ( P < .001) as compared with surgeon‐guided procedures. The mean error in sagittal plane alignment was not significantly different ( P = .321), but variability in alignment was significantly lower when navigation was used ( P = .008). Conclusion: Surgical navigation significantly improved accuracy and decreased variability in tibial component alignment in canine TKR. Clinical trials would be required to determine whether these improvements in surgical accuracy lead to better clinical outcomes in terms of joint function and a reduction in long‐term implant wear.